Pengaruh Struktur Modal, Kebijakan Dividen dan Ukuran Perusahaan Terhadap Nilai Perusahaan : (Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023) - Amanda, Elsa; Kosim, Belliwati; Hidayat, Randy (Economics and Digital Business Journal, 2024)
This study aims to determine the effect of Capital Structure, Dividend Policy and Company Size on the Value of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange. The type of research used is Descriptive. A sample of 6 food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The data used is secondary data obtained from the official website www.idx.co.id or through the website of the company being studied. The data collection method used is documentation analysis. The analysis technique used is quantitative. Then a statistical analysis was carried out using Financial Analysis, Classical Assumption Test, Multiple Linear Regression and Hypothesis Testing which includes the F Test and t Test. The results of this study indicate that there is a significant influence of capital structure, dividend policy and company size simultaneously on company value, there is a partial influence of capital structure and company size on company value.